Intelligent wearable interfaces - Xu, Yangsheng; Lee, Ka Keung Caramon; Li, Wen J (Wiley-Interscience, 2007)
A thorough introduction to the development and applications of intelligent wearable interfaces As mobile computing, sensing technology, and artificial intelligence become more advanced and their applications more widespread, the area of intelligent wearable interfaces is growing in importance. This emerging form of human-machine interaction has infinite possibilities for enhancing humans' capabilities in communications, actions, monitoring, and control. Intelligent Wearable Interfaces is a collection of the efforts the authors have made in this area at The Chinese University of Hong Kong. They introduce methodologies to develop a variety of intelligent wearable interfaces and cover practical implementations of systems for real-life applications. A number of novel intelligent wearable interface systems are examined, including: Network architecture for wearable robots Wearable interface for automatic language translation Intelligent cap interface for wheelchair control Intelligent shoes for human-computer interface Fingertip human-computer interface Ubiquitous 3D digital writing instrument Intelligent mobile human airbag system This book is a valuable reference for researchers, designers, engineers, and upper-level undergraduate and graduate students in the fields of human-machine interactions,rehabilitation engineering, robotics, and artificial intelligence.